The Development of the Competency of Phrapariyattidhamma Schools, General Education Section, - (Saeng Aphiwanno), Phrakhu Prariyatjatiyakun; Saññato , PhramahaSamrong; Saengsai, Prayoon (Journal of Modern Learning Development, 2022)
This academic article has purpose to present the development of competency of Phrapariyattidhamma Schools, generation education section. The result of study found that it was transmission, exchange, knowledge distribution, information storage, development in various field including skill, attitudes, values leadership characteristics, motivation or internal driving and use it as a strategy for formulate and action plan to develop network building performance according to the rules. The collective agreement stipulate. Every action is monitored and evaluated for the development of network building capacity, relationships, intimacy, harmony, clarity of the goods which are not based on member opinions. The process of presenting opinions and making decisions sources of resources learning potential and innovation, diversity coming together of members.